Potensi Bakteri Pseudomonas stutzeri dari Objek Wisata Pusat Laut, Kabupaten Donggala sebagai Antibakteri terhadap Staphylococcus aureus - Slamet Ifandi; Shinta Nugraini; Enggar Enggar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Pusat Laut is a tourist area located in Towale Village, Banawa Tengah District, Donggala Regency. The purpose of the study was to determine the antibacterial activity of Pseudomonas stutzeri against Staphylococcus aureus skin disease bacteria. This type of research is qualitative with descriptive analysis with data interpretation presented in tabular form. The results of the study showed that P. stutzeri bacteria were able to inhibit Staphylococcus aureus pathogenic bacteria with an average inhibition zone of 10ab (mm). This study can provide scientific evidence of the potential of marine bacteria, especially in the fields of biotechnology and pharmacy as antibiotic drug ingredients in the future.